The devil's doctor : Felix Kersten and the secret plot to turn Himmler against Hitler - Waller, John H., 1923- 1923- (Wiley, 2002)
Tells the story of Felix Kersten, a physical therapist who became Heinrich Himmler's personal physician, and his influence over Himmler to join a plot to overthrow Adolf Hitler.